Frog Assemblage - Ramlah, Zainudin; Elvy Quatrin, Deka; MUHAMMAD FADZIL, AMRAM; NUR AMIRAH, MD SUNGIF; SHARIZATTY, MOHD. RAIS; MARLY MATHLEEN, AUGUSTINE AGOH; NOORAINA ATIRA, Alaudin; MOHAMAD AMIRUL, AZMI (UNIMAS Publisher and Wilmar Plantations Sdn Bhd., 2023)
About half of Bornean amphibians are endemic to the island, being restricted to specific habitats, from lowland dipterocarps to submontane forests. They tend to be sensitive to their environment and water quality in particular and thus, can serve as good environmental indicators. Negative changes in water quality are known to cause a higher rate of tadpole fatality and deformation. Berry et al. (2010) revealed that logging has adversely affected amphibian abundance. Thus, the anuran is an ideal indicator of ecosystem health. Many large plantations have set up High Conservation Value (HCV) areas to provide a network of wildlife refuges that may have once inhabited pristine and undisturbed forests, complying with international code of conduct for such plantations. The HCV forest thus functions to maintain or enhance biodiversity values within homogenous vegetation. The impact of rainforest degradation due to its conversion to oil palm plantations on amphibians is relatively unknown. Additionally, information on anuran communities in oil palm plantations is still limited to a few studies to date (Gillespie et al., 2012; Faruk et al., 2013; Norhayati et al., 2014; Zainudin et al., 2019). Faruk et al. (2013) found that anuran communities in plantations consisted of species that thrive in disturbed areas. Furthermore, Harrison and Bruna (1999) stated that fragmented habitats cannot simply represent the original habitat and that their biotas may be altered to a great extent, thus assuming that conserving small remnant areas will not guarantee species conservation. Anurans are susceptible to habitat change, thus, their community ecology would be potentially affected if natural habitats are modified and / or altered by human disturbances. With previous findings as well as the sensitivity of the anurans, it is important to assess the connectivity of the frog assemblages at HCV areas. The assemblages structure of anurans along the established HCV areas at Bukit Durang, Wilmar Plantations were documented in this chapter. It will provide insight into the function of HCV areas for the conservation of biodiversity maintenance in large oil palm plantations.